Benjamin's Chinese Painter: Copying, Adapting, and the Aura of Reproduction. Issue 1 (2nd January 2019) - Cao, Jan
Abstract : In his famous "artwork" essay, Walter Benjamin uses the legend of a Chinese painter who disappeared into his own painting as the example par excellence of traditional art reception, performed through "concentration" and individual absorption, as opposed to distraction—the form of reception associated with contemporary mass media such as films. By exploring the historical background of this legend, this essay aims at developing a new perspective of Benjamin's theory of mechanically reproducible art and the decline of aura. Locating the origin of the legend of the Chinese painter in Edo Japan, a period of mass-produced works of art and entertainment, I argue that the aura that Benjamin associates with this legend is, ironically, a result of mechanical reproduction. By appropriating ancient Chinese esthetic principles to justify his method of copying, adapting, and transmitting, Edo print maker and model book author Tachibana Morikuni redefined the concept of reproduction as a way to recreate the "mysterious beauty and spiritual wonder" of the original, a concept that is arguably comparable to Benjamin's "aura."